PENGGUNAAN MODEL PROBLEM BASED LEARNING DALAM MENUMBUHKAN SIKAP KEBANGSAAN PADA PEMBELAJARAN PKn - Abdul Gani; Pargito Pargito; Irawan Suntoro (Faculty of Teacher Training and Education, University of Lampung, 2013)
This classroom action research aims to ascertain the nationality growth of the attitude in Citizenship Education by using a model of problem-based learning in civics. This type of research is a classroom action research which is done to increase the student’s nationality, the strengths and weaknesses of teachers and students in the learning process. The results that obtained show that Problem based learning can foster student’s nationality attitudes and Problem based learning can foster the creativity of the teachers. In the first cycle, 20 students have the nationality attitude with an average value of 62 % . The second cycle shows the enhancement of the 24 students with an average value 74 % and the nationality attitude of the third cycle keep growing up, 28 students with an average value of 86 % from 32 students overall.Penelitian tindakan kelas ini bertujuan untuk mengetahui pertumbuhan sikap Kebangsaan siswa dalam pembelajaran Pendidikan Kewarganegaraan dengan menggunakan model Problem Based Learning. Jenis penelitian ini adalah Penelitian Tindakan kelas yang dilakukan untuk menumbuhkan sikap kebangsaan siswa, kekurangan dan kelebihan guru, serta siswa dalam proses pembelajaran. Hasil penelitian yang di peroleh menunjukkan bahwa model problem based learning dapat menumbuhkan sikap kebangsaan siswa dan model problem based learning dapat menumbuhkan kreativitas guru. Pada siklus I, 20 siswa memiliki sikap kebangsaan dengan rata-rata nilai 62%, siklus II menunjukan pertumbuhan yaitu 24 siswa atau rata-rata nilai 74%, dan pertumbuhan sikap kebangsaan siswa semakin meningkat pada sisklus III, yaitu 28 siswa dengan rata rata nilai 86 % dari jumlah peserta didik secara keseluruhan yaitu 32 siswa. Kata kunci: pkn, problem based learning, sikap kebangsaan